2016
DOI: 10.1002/ange.201607237
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Carbon–Carbon Bond Breaking and Spin Equilibria in Bis(pyrimidinenorcorrole)

Abstract: Reversible homolytic dissociation of the bis(pyrimidinenorcorrole) σ‐dimer was elucidated by means of variable temperature ESR and 1H NMR spectroscopy, mass spectrometry, and optical spectrocopy. Dehydrogenation of the σ‐dimer yielded another dimer displaying a singlet–triplet equilibrium in solution, strong NIR absorption (1570 nm), and a narrow electrochemical HOMO–LUMO gap (0.74 V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…It exhibits extensive spin delocalization in its 139-electron π system and spontaneously dimerizes into a stable σ-dimer, which is susceptible to photochemical rather than thermal cleavage. Such a selectivity is untypical: dissociation of σ-dimers in solution is usually induced thermally 2 10 , 27 , 28 or, occasionally, by each of these stimuli. 68 Herein, the switching between the radical and its σ-dimer relies on homolytic rupture of a weak C(sp 3 )–C(sp 3 ) bond but is controlled by a balance between π-conjugative stabilization, internal strain, 69 and nonbonding interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It exhibits extensive spin delocalization in its 139-electron π system and spontaneously dimerizes into a stable σ-dimer, which is susceptible to photochemical rather than thermal cleavage. Such a selectivity is untypical: dissociation of σ-dimers in solution is usually induced thermally 2 10 , 27 , 28 or, occasionally, by each of these stimuli. 68 Herein, the switching between the radical and its σ-dimer relies on homolytic rupture of a weak C(sp 3 )–C(sp 3 ) bond but is controlled by a balance between π-conjugative stabilization, internal strain, 69 and nonbonding interactions.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 11 , 25 28 Among recent examples, nickel(II) pyrimidinenorcorrole radical 1 • ( Chart 1 ) regioselectively forms a σ-dimer that reversibly dissociates upon heating in solution. 27 The (β-porphyrinyl)dicyanomethyl radical 2 • showed temperature-dependent exocyclic σ-dimerization, while its meso -porphyrinyl isomer was found not to dimerize at all. 5 Similarly, the azabuckybowl radical cation 3 • was observed to σ-dimerize in the solid state and in solution at low temperatures, whereas only π-dimerization was observed for its near-planar analogue.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have already demonstrated that the position, number and valence of N atoms in the frameworks of azaacenes have strong effects on the properties of as‐resulted azaacenes . Nowadays, most of the azaacenes were constructed by the insertion of pyrazine N‐heterocycle, other N atoms containing heterocycles such as pyridine, pyridazine, pyrimidine, etc, although have been investigated widely in other organic materials, were relatively investigated less in acenes,, which may exhibit some interesting and even special properties. For example, Zhang's group reported several pyridine‐containing azapentacenes, which exhibit balanced electron and hole mobilities ,.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Synthesis of chlorin dimers (9) 2 is outlined in Scheme 1. 2,18-Bis(dicyanomethyl)-substituted Ni II -porphyrin 8 was prepared in 64 % yield by Pd-catalyzed coupling reaction of 2,18-diiodo-Ni II -porphyrin precursor 7 [10] with malononitrile in the presence of sodium hydride in 1,2-dimethoxyethane (DME) at 80 8C. Porphyrin 8 is stable, showing the parent ion peak at m/z = 1058.5224 (M + ) (calcd for [C 68 H 72 N 8 Ni] + = 1058.5228) by high-resolution atmospheric-pressure-chemical-ionization time-of-flight (HR-APCI-TOF) mass spectrometry.…”
mentioning
confidence: 99%
“…At 418 K, the spectrum became considerably broad in all the range, suggesting the generation of a considerable amount of radical in solution. [10] In the next step, we examined the synthesis of the Zn II counterpart of the chlorin dimer. We attempted the coupling reaction of 2,18-diiodo-Zn II -porphyrin precursor 10 [11] with sodium malononitrile under the similar conditions but could Scheme 1.…”
mentioning
confidence: 99%